1997
DOI: 10.1023/a:1018409422050
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Epidemiologic evidence on the relationship between mineral oil exposure and cancer is reviewed. The review is restricted to occupations involving substantial dermal and inhalational exposure and for which an epidemiologic literature exists: metal machining, print press operating, and cotton and jute spinning. Mineral oils are complex mixtures of aliphatic hydrocarbons, naphthenics, and aromatics, the relative distribution of which depends on the source of the oil and the method of refinement. End-use products … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(16 citation statements)
references
References 81 publications
0
16
0
Order By: Relevance
“…Some previous studies (6, 8, 9, 11) showed elevation of stomach cancer in foundry workers. The known occupational risk factors of stomach cancer include asbestos, metalworking fluids and other oil mist (2, 26). Among some foundry work, workers in the fettling shop are exposed to these kinds of hazards besides silica and heavy metals.…”
Section: Discussionmentioning
confidence: 99%
“…Some previous studies (6, 8, 9, 11) showed elevation of stomach cancer in foundry workers. The known occupational risk factors of stomach cancer include asbestos, metalworking fluids and other oil mist (2, 26). Among some foundry work, workers in the fettling shop are exposed to these kinds of hazards besides silica and heavy metals.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, many of the pollutants released by industries are carcinogens, and some of these have been associated with tumours of the digestive system [11]. Occupations too have been described as being specifically associated with tumours of the colon and rectum incidence [12].…”
Section: Introductionmentioning
confidence: 99%
“…The evidence for an increased risk of lung cancer in workers exposed to mineral oils varies with studies of metalworkers generally showing negative results, and studies of workers in the printing industry showing increases (Tolbert, 1997). A combined estimate of RR from seven studies reviewed by Tolbert (1997) gave an RR of 1.6 (95% CI 1.3, 1.9; Rushton et al, 2008).…”
Section: Mineral Oilsmentioning
confidence: 99%
“…Several bladder cancer case-control studies have found an association with work as a machinist, with studies of workers using metalworking fluids and mineral oils offering strong evidence for an association with bladder cancer (Calvert et al, 1998;Tolbert, 1997). An overall RR for bladder cancer from exposure to mineral oils across the case-control and population-based studies from Tolbert's review is 1.39 (95% CI 1.20, 1.61; Rushton et al, 2008).…”
Section: Mineral Oilsmentioning
confidence: 99%